The Impact of Source and Use of Funds on Liquidity at PT. Mustika Ratu Tbk - Rudi Sanjaya (Prodi Manajemen Universitas Pamulang, 2020)
The purpose of this research is to know the source and use of funds at PT. Mustika Ratu, to find out Liquidity of PT. Mustika Ratu Tbk and to know the influence of sources and the use of funds to liquidity at PT. Mustika Ratu Tbk.Research methods used is a quantitative descriptive that is doing discussion of the problems faced to the company's performance of financial aspects. the analytical data used are data that is data are numeric. Samples used in this study i.e. balance sheet, Profit and loss report on PT. Mustika Ratu Tbk Year 2010 to with 2013. The qualitative data i.e. data not stated in the form of numbers, like a brief history of PT. Mustika Ratu Tbk and business field of PT. Mustika Ratu Tbk. Determining whether a relationship is between the source and the use of funds at PT. Mustika Ratu Tbk with liquidity used method of regression equation analysis, coefficient of determination and test of significance.Result of source influence and use of funds with liquidity the presence of strong relationships and between the source and the use of funds and liquidity means having a relationship has a direct relationship. The magnitude of the source relationship the use of funds with liquidity 92.16% which means that the source and the use of funds affects the Sufficient liquidity. While the rest which is 7.84% influenced by factors other causes. In this case the source and use of funds (92.16%) describe that PT. Mustika Ratu Tbk has a fairly good relationship in the improve the company's financial performance. Other factors (7.84%). Based on test hypothesis, it is known that based on results calculation of the research T count Smaller than t table 3.42 < 6.31 then Ho accepted and Ha is rejected meaning that hypotheses the source and use of funds not have a convincing relationship (not significant) with liquidity.